Diagnostic challenges and clinical insight of medial thigh hemangiolymphangioma in adult: A rare case report - Rizkiani, Dwinanda Almira; Trisnowati, Niken; Khalidah, Miya; Anggatama, Marcella; Dyah Ayu Mira Oktarina (Published by Universitas Gadjah Mada, 2025)
Vascular anomalies are classified into vascular tumors and vascular malformations. Hemangiolymphangioma (HLA) is a rare vascular malformation that contains both blood and lymphatic components, most commonly diagnosed in infancy or early childhood. Adult cases, especially in atypical locations such as the medial thigh, are exceedingly rare and pose diagnostic challenges. A 27 yo female presented with a slowly enlarging, painless lump on the left medial thigh. Initially misdiagnosed as condyloma acuminata, the lesion was subsequently identified as a vascular malformation through dermoscopic visualization of characteristic vascular lacunae. Histopathological and immunohistochemical analyses confirmed the diagnosis of HLA. Surgical excision was performed with clear margins, and no recurrence was observed after 3 mo. Hemangiolymphangiomas are benign but may exhibit local infiltration and recurrence, especially after incomplete resection. Diagnosis requires a multimodal approach including clinical assessment, dermoscopy, histopathology, and immunohistochemistry. Differential diagnosis includes hemangioma, lymphangioma, and malignancies such as lymphangiosarcoma. Complete surgical excision remains the treatment of choice, with other modalities like electrocautery or cryotherapy considered in selected cases. Long-term follow-up is crucial due to the risk of recurrence. In conclusion, this rare adult case of medial thigh HLA highlights the importance of considering vascular malformations in atypical anatomical sites. Early recognition and comprehensive diagnostic evaluation facilitate appropriate management and improve patient outcomes